Peran Program Perpustakaan Keliling sebagai Layanan Publik di Perpustakaan Umum Kota Cimahi: Pendekatan Kualitatif - Tamiati, Fani Yasta Viora; Erwina, Wina; Perdana, Fitri (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study examines the role of the mobile library program as a form of public service provided by the Cimahi City Public Library in enhancing literacy access for the community, particularly for students in areas with limited access to conventional libraries. The study is motivated by the urgency of equitable access to information as a part of inclusive literacy development. This research employs a descriptive qualitative method, with data collected through in-depth interviews with librarians who are directly involved in the implementation of the program. The findings indicate that the mobile library significantly contributes to increasing students’ reading interest by providing diverse and easily accessible reading materials. The presence of this service allows students to access information without the need to visit a library building directly. However, the implementation of the program faces several challenges, including limited vehicle availability, a shortage of human resources, and the risk of collection damage due to high mobility. Nevertheless, the findings suggest that the mobile library plays a strategic role in expanding the reach of library services and supporting the development of an equitable literacy ecosystem in Cimahi City.